1991
DOI: 10.1172/jci115148
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cobalamin-dependent enzymes by cobalamin analogues in rats.

Abstract: To determine which parts of the cobalamin (cbl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 34 publications
3
51
1
1
Order By: Relevance
“…Thus, at the highest concentration of cobinamide tested, the cobinamide concentration was 400 times that of the deoxyadenosylcobalamin concentration. The lack of inhibition of either enzyme by cobinamide is consistent with studies reported by others on various cobalamin analogs including cobinamide (47,48).…”
Section: Efficacy Of Cobinamide As a No Scavenger In A Drosophilasupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, at the highest concentration of cobinamide tested, the cobinamide concentration was 400 times that of the deoxyadenosylcobalamin concentration. The lack of inhibition of either enzyme by cobinamide is consistent with studies reported by others on various cobalamin analogs including cobinamide (47,48).…”
Section: Efficacy Of Cobinamide As a No Scavenger In A Drosophilasupporting
confidence: 91%
“…Previous studies have found little or no toxicity of cobinamide to mammalian cells, but these studies were done at low micromolar or submicromolar concentrations of the drug (48,72,73). We similarly found no toxicity of cobinamide to mammalian cells at low micromolar concentrations but began to observe toxicity at a concentration of about 50 M. Because each cobinamide molecule can potentially neutralize two NO molecules (22), cobinamide may be able to neutralize NO concentrations up to 100 M before exhibiting significant toxicity.…”
Section: Discussionsupporting
confidence: 64%
“…Earlier efforts have used nutritional [16] and cobalamin-analog treatments [17] to induce methylmalonic aciduria in rats. Both of these treatments are artificial and produce an incomplete block, especially in the case of nutritional deficiency, causing combined methionine synthase and methylmalonylCoA mutase functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated effects of the dodecylamine derivative of OH-Cbl (1.0 μmol/L) on total and holo-MCM activities of the cells grown in OH-Cbl (at 0, 0.1, and 1.0 μmol/L)-supplemented medium, compared with the OH-Cbl [c-lactam] that is known as the Cbl-dependent enzyme inhibitor [8] [9]. When total MCM activity was significantly decreased with increase in concentration of the added OH-Cbl, 1.0 μmol/L dodecylamine and c-lactam derivatives did not affect the total enzyme activity at each concentration of authentic OH-Cbl (Figure 4).…”
Section: Effect Of the Oh-cbl Dodecylamine Derivative And Oh-cbl [C-lmentioning
confidence: 99%
“…The Cbl analogue with a modification of the side chain of C-ring, Cbl [c-lactam], has been reported to antagonize Cbl in the cultured HL 60 cells [8]. Subcutaneous administration of hydroxocobalamin (OH-Cbl) [c-lactam] to rats has indicated that the analogue has the ability to act as a potent inhibitor of the mammalian Cbl-dependent enzymes to make the rats Cbl-deficient [9]. However, considerably high concentration of OH-Cbl [c-lactam] must be administrated for several weeks with osmotic mini pumps in order to prepare Cbl-deficient rats because IF hardly binds OH-Cbl [c-lactam] [9].…”
Section: Introductionmentioning
confidence: 99%